High temperature reactions of boron oxide and nickel with copper (I and II) or silver oxide - (:unkn) unknown (COUNCIL SCIENTIFIC INDUSTRIAL RESEARCH, 1997)
The high temperature reactions between boron oxide and oxides of Cu(I), Cu(II) and Ag(I) have been investigated in a nickel crucible at 1100 degrees C in air. The ternary systems containing metallic nickel gave glassy products in two layers. Compositions of the fusion products have been determined by XRD, SEM, TEM, IR and chemical analyses and reaction pathways have also been elucidated. The reactions between CuO and B2O3 yield Cu2O and only Cu(I) berates, CuBO2 or a -Cu2B4O7, instead of Cu(II) berates, indicating predominant decomposition of CuO into Cu2O. The glasses obtained from Cu2O and B2O3 give Cu(l) metaborate and the unexpected Cu(II) metaborate CuO . B2O3 which can be decomposed to yield Cu2O and CuBO2. From the ternary Ag2O-B2O3-Ni system, the only berates obtained are nickel borates. Nickel borates, unexpectedly rich in NiO content, 2NiO. B2O3 or 3NiO. B2O3, are observed in most glasses. Although the products do not show any significant electrical conductivity or magnetic properties, the hardness of material increases due to the presence of CuBO2, beta-Cu2B4O7 or CuB2O4. By controlling the reaction conditions the formation of such compounds can be ensured to obtain harder materials.